Developing of Drama Teaching Materials with Benime Assisted for High School Students - Trisnawati Hutagalung; Dwi Friska Br. Girsang; Novhira Putri Paino (Studies in Learning and Teaching, 2023)
This research and development is to find out the product development process and feasibility, as well as to find out the effectiveness of the drama material development product using the Benime application for class XI students at SMA Negeri 1 Hamparan Perak. The process of developing drama material uses the Benime application in the form of audiovisual teaching materials using the stages of the R&D method by Borg and Gall with 8 research stages covering 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) small-scale trials, 7) product revisions, and 8) mass production. From the validation results obtained a score calculation from material experts of 82% very good "and media experts of 97% "very good". The results of the validation assessment of product feasibility have very good quality to use. one group pretest-posttest design 20 multiple-choice test questions. Data analysis used the Normalized Gain Test. The results showed that the total pretest score of all students was 1760 and the total posttest score of all students was 2485. The results were processed using the formula N-Gain and achieved a value of 0.58 with the interpretation of "Medium" this result there is a significant increase in student achievement by using Benime-based teaching materials in class XI students.